2017
DOI: 10.1016/j.neuroscience.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Klotho regulates CA1 hippocampal synaptic plasticity

Abstract: Global klotho overexpression extends lifespan while global klotho-deficiency shortens it. As well, klotho protein manipulations inversely regulate cognitive function. Mice without klotho develop rapid onset cognitive impairment before they are 2 months old. Meanwhile, adult mice overexpressing klotho show enhanced cognitive function, particularly in hippocampal-dependent tasks. The cognitive enhancing effects of klotho extend to humans with a klotho polymorphism that increases circulating klotho and executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
35
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 56 publications
12
35
2
3
Order By: Relevance
“…Since KL is not detected until late embryonic development (Takeshita et al 2004), it is unlikely that neural stem cells express KL protein. Consistent with previous reports (Clinton et al 2013; Li et al 2017), the highest expression of KL is measured in choroid plexus cells but mature neuronal layers of the hippocampus, including the dentate also express KL protein (Figure 3E). KL expression is prominent in mature neuronal processes as evidenced by a gradient of increasing KL expression with lowest KL reactivity occurring in SGZ (Figure 3E).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Since KL is not detected until late embryonic development (Takeshita et al 2004), it is unlikely that neural stem cells express KL protein. Consistent with previous reports (Clinton et al 2013; Li et al 2017), the highest expression of KL is measured in choroid plexus cells but mature neuronal layers of the hippocampus, including the dentate also express KL protein (Figure 3E). KL expression is prominent in mature neuronal processes as evidenced by a gradient of increasing KL expression with lowest KL reactivity occurring in SGZ (Figure 3E).…”
Section: Resultssupporting
confidence: 93%
“…We measured KL’s expression profile during dentate development using mRNA isolated from wild-type (WT) hippocampi embryonic day 17 (E17) to 8 weeks of age. Using a primer/probe set to allow detection of all KL forms, we found that hippocampus achieved adult level KL expression by 3 weeks of age (Figure 1A), consistent with the reported expression of KL mRNA and protein in mature neurons (Clinton et al 2013; Li et al 2017). …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…7a). When comparing wild type mice and klotho overexpressing mice (WT, OE) (28), the later group showed increased klotho mRNA levels in the lung, which was independent of smoke exposure (Fig. 7b).…”
Section: Resultsmentioning
confidence: 91%